Immunogenicity and safety of a hexavalent pediatric vaccine in HIV-exposed infected and uninfected infants in Republic of South Africa - Anthonet Koen; Shabir Madhi; Olga Lyabis; Emmanuel Vidor; Beverley Cowper; Thinus Marais; Dhaval Patel; Claire Vigne (Human Vaccines & Immunotherapeutics, 2021)
Human immunodeficiency virus (HIV)-exposed infants may be at increased risk of vaccine-preventable disease. This study was conducted as a post-licensure commitment in this population to evaluate the primary series, antibody persistence, and booster response to a licensed fully liquid hexavalent vaccine containing diphtheria (D), tetanus (T), acellular pertussis (aP), inactivated poliovirus (IPV), hepatitis B (HB), and Haemophilus influenzae type b antigens (PRP~T). This was a Phase III, open-label, randomized study conducted at a single center in the Republic of South Africa. The DTaP-IPV-HB-PRP~T vaccine was administered to HIV-exposed infected (Group A: N = 14) and HIV-exposed uninfected (Group B: N = 50) infants as a 6, 10, 14 week primary series with a toddler booster at 15–18 months of age. Immunogenicity of each antigen was measured using validated assays and vaccine reactogenicity was recorded using diary cards. The low number of HIV-exposed infected participants, due to widespread pre- and peri-natal retroviral treatment, meant that between-group comparisons should be treated with caution. In each group, primary series and booster immune seroprotection rates were strong, and pre-booster antibody persistence was good, although anti-HBs ≥10 mIU/mL in Group A was 78.6% post-primary series, 58.3% pre-booster, and 75.0% post-booster. There were no safety concerns. In conclusion, primary series and booster vaccination of the DTaP-IPV-HB-PRP~T vaccine were immunogenic and safe in HIV-exposed infected and uninfected infants. These results were comparable to historical data in healthy infants and toddlers.